Upaya Kepala Madrasah Dalam Mengatasi Problematika Guru Tentang Penerapan Kurikulum 2013 Di MTS Ainul Hasan Wonorejo Maron Probolinggo - Rahayu, Eka; Nur Jannah, Siti (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2020)
ABSTRACT The curriculum is the most important thing in the world of education, without a curriculum an educational institution will not run well. This article aims to determine the efforts of madrasah principals in overcoming teacher prolematics regarding the implementation of the 2013 curriculum. Data collection was carried out using observation, interview and documentation methods. While the data analysis used descriptive qualitative. The results showed that the problems faced by teachers at MTs Ainul Hasan in implementing the 2013 curriculum were not so heavy, because the efforts made by the principal of MTs Ainul Hasan were to professionalize teachers by holding 2013 curriculum training held at the madrasah itself and outside the madrasah, complementing the facilities. and existing infrastructure as well as supervising the running of PBM. Keywords: principal, teacher problems, curriculum 2013